2011
DOI: 10.5194/os-7-63-2011
|View full text |Cite
|
Sign up to set email alerts
|

Salinity-induced mixed and barrier layers in the southwestern tropical Atlantic Ocean off the northeast of Brazil

Abstract: These results indicate that the inclusion of salinity dynamics and its variability are necessary for studying mixed and barrier layer behaviors in the tropical Atlantic, where ocean-atmosphere coupling is known to be stronger.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 32 publications
1
20
0
Order By: Relevance
“…During June-July, which corresponds in the following to the core rainy season at Recife (ENEB), higher equatorial SST (>27 ∘ C) presents a northward displacement as a result of the northward shifting of the ITCZ (Figure 1(b), bottom panel). However, the SAWP (black box in (a) and in the bottom panel of (b)) shows weak variation of SST (>27 ∘ C) with a seasonal variability less than 2 ∘ C [29][30][31][32][33]. This region also presents weak interannual SST variability, where the standard deviation of monthly anomalies is 0.2-0.3 ∘ C (Figure 1(a)).…”
Section: Surface Meteorological Data: Rainfall Sst and Pwsmentioning
confidence: 99%
See 2 more Smart Citations
“…During June-July, which corresponds in the following to the core rainy season at Recife (ENEB), higher equatorial SST (>27 ∘ C) presents a northward displacement as a result of the northward shifting of the ITCZ (Figure 1(b), bottom panel). However, the SAWP (black box in (a) and in the bottom panel of (b)) shows weak variation of SST (>27 ∘ C) with a seasonal variability less than 2 ∘ C [29][30][31][32][33]. This region also presents weak interannual SST variability, where the standard deviation of monthly anomalies is 0.2-0.3 ∘ C (Figure 1(a)).…”
Section: Surface Meteorological Data: Rainfall Sst and Pwsmentioning
confidence: 99%
“…Since the seasonal evolution of the Ocean-atmosphere variables is generally related to the Ocean subsurface features such as depth of warm water, we estimated the isothermal layer depth (ILD) and the barrier layer thickness (BLT) in order to analyze their potential influence on the strong rainfall variability. We chose to estimate both the ILD and the BLT because previous studies have shown their importance on the seasonal evolution of the Ocean-atmosphere variables in the western equatorial Atlantic (offshore of NEB) [34][35][36].…”
Section: Subsurface Ocean Data: Isothermal Layer Depth (Ild)mentioning
confidence: 99%
See 1 more Smart Citation
“…E is the sum of kinetic and potential energy per unit of horizontal area. In north-eastern of Brazil, the average surface water salinity is 36 (Araujo et al, 2011) and the mean temperature is 26°C (Mehta et al, 1995), leading to a water density of approximately 1023 kg/m 3 .…”
Section: Numerical Modellingmentioning
confidence: 99%
“…Finally, we decided to retain an error norm of 0.02 to estimate the MLD at each Argo profile in this study. As in previous studies, which estimated mean seasonal and/or climatological MLD variability (e.g., Araujo et al, 2011;de Boyer Mont egut et al, 2004;Vauclair & du Penhoat, 2001), this value is assumed to be representative of the mean MLD estimates using density profiles.…”
Section: Mixed-layer Depth (Mld)mentioning
confidence: 99%